Meet the parents - De Niro, Robert; Stiller, Ben, 1965-; Polo, Teri, 1969-; Roach, Jay.; Universal Pictures (Firm) (Universal City, Calif. : Universal, 2001)
Greg Focker will be proposing to his girlfriend Pam while they are visiting her parents. But he must ask her father first.
Includes theatrical trailer, production notes, outtakes, deleted scenes with commentary, feature commentary with cast and crew.
Director, Jay Roach ; producers, Nancy Tenebaum, Jane Rosenthal, Robert De Niro & Jay Roach ; screenplay, Jim Herzfeld & John Hamburg ; story, Greg Glenna & Mary Ruth Clarke ; music, Randy Newman.
Robert De Niro, Ben Stiller, Blythe Danner, Teri Polo, James Rebhorn, Jon Abrahams, Owen Wilson.
Rated PG-13.
DVD format ; full screen edition.
Closed-captioned for the hearing impaired.
Keywords: Comedy films; Feature films; Films for the hearing impaired